2010
DOI: 10.1007/s10641-010-9655-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy allocation in juveniles of a warm-temperate reef fish

Abstract: During the first year of life, organisms are faced with competing demands for energy between growth and storage. Most research on energy allocation in young fishes has focused on cold-temperate species which are subjected to strong seasonal fluctuations in productivity, while few studies have considered those at lower latitudes where seasonality is less pronounced. Gag (Mycteroperca microlepis) of the northeastern Gulf of Mexico settle in coastal seagrass beds in the spring as juveniles and emigrate to offshor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…RNA/DNA and lipid data were transformed (natural log and square root, respectively) to meet regression assumptions of normally distributed residuals and equal variances. A piecewise regression approach was used because we expected the energy allocation strategy could shift at a fixed length for juvenile herring, as has been observed for other juvenile fishes in seasonal environments (Post & Parkinson 2001, Stallings et al 2010). In addition, exploratory analysis of November data using generalized additive models (GAMs; Wood 2006) suggested that the slopes of the relationships between RNA/DNA or % lipid and length were not linear and changed abruptly at intermediate lengths.…”
Section: Size-based Trade-offs Between Growth and Energy Storagementioning
confidence: 99%
“…RNA/DNA and lipid data were transformed (natural log and square root, respectively) to meet regression assumptions of normally distributed residuals and equal variances. A piecewise regression approach was used because we expected the energy allocation strategy could shift at a fixed length for juvenile herring, as has been observed for other juvenile fishes in seasonal environments (Post & Parkinson 2001, Stallings et al 2010). In addition, exploratory analysis of November data using generalized additive models (GAMs; Wood 2006) suggested that the slopes of the relationships between RNA/DNA or % lipid and length were not linear and changed abruptly at intermediate lengths.…”
Section: Size-based Trade-offs Between Growth and Energy Storagementioning
confidence: 99%
“…Total lipid content and lipid class composition of muscle, liver and gonad tissues were analysed to measure the allocation of energetic reserves to growth, storage and reproduction respectively (Stallings, Coleman, Koenig, & Markiewicz, 2010;Zudaire et al, 2014) (see supporting information for detailed methods). Concentrations of triacylglycerols (TAG), free sterols (ST), and phospholipids (PL) were measured as μg/mg of wet weight (ww) (Parrish, 1999).…”
Section: Lipid Analysismentioning
confidence: 99%
“…1998). These habitats also serve as important nursery areas, and as juveniles increase in size they leave the protection of seagrass beds and move into hard bottom habitats nearshore in the Gulf of Mexico (Stallings et al, 2010). Due to their life history and the high concentration of recreational fisheries in lower estuaries and nearshore, gags are vulnerable to fishing pressure at a young age.…”
Section: List Of Figuresmentioning
confidence: 99%